Refractory functional constipation: clinical management or appendicostomy? - Vanesca P.A. de Arruda; Maria A. Bellomo‐Brandão; Joaquim M. Bustorff‐Silva; Elizete Aparecida Lomazi (Brazilian Society of Pediatrics, 2020)
Objective: To compare the clinical evolution in patients with refractory functional constipation undergoing different therapeutic regimens: oral laxatives and antegrade enemas via appendicostomy or clinical treatment with oral laxatives and rectal enemas. Methods: Analysis of a series of 28 patients with a mean age of 7.9 years (2.4-11), followed‐up in a tertiary outpatient clinic. Refractory functional constipation was defined as continuous retentive fecal incontinence after at least a 12‐month period of consensus therapy. After the diagnosis of refractory condition, appendicostomy was proposed and performed in 17 patients. Outcomes: (1) persistence of retentive fecal incontinence despite the use of enemas, (2) control of retentive fecal incontinence with enemas, and (3) control of retentive fecal incontinence, spontaneous evacuations, with no need for enemas. Results: Six and 12 months after the therapeutic option, control of retentive fecal incontinence was observed only in patients who underwent surgery, 11/17 and 14/17, p = 0.001 and p = 0.001, respectively. At 24 months, control of retentive fecal incontinence was also more frequent in operated patients: 13/17 versus 3/11 with clinical treatment, p = 0.005. In the final evaluation, the median follow‐up times were 2.6 and 3 years (operated vs. clinical treatment, p = 0.40); one patient in each group was lost to follow‐up and 9/16 operated patients had spontaneous bowel movements vs. 3/10 in the clinical treatment group, p = 0.043. Surgical complications, totaling 42 episodes, were observed 14/17 patients. Conclusion: Appendicostomy, although associated with a high frequency of complications, controlled retentive fecal incontinence earlier and more frequently than clinical treatment. The choice of one of the methods should be made by the family, after adequate information about the risks and benefits of each alternative. Resumo: Objetivo: Comparar a evolução clínica em crianças com constipação intestinal funcional refratária sob diferentes regimes terapêuticos: laxativos orais e enemas anterógrados via apendicostomia ou tratamento clínico com laxativos orais e enemas via retal. Métodos: Análise de uma série de 28 pacientes, 7,9 anos (2,4‐11), acompanhados em ambulatório terciário. Constipação intestinal funcional refratária foi definida como manutenção da incontinência fecal retentiva, em terapia consensual, por pelo menos 12 meses. Após diagnóstico de refratariedade, era proposta apendicostomia. Dezessete pacientes realizaram o procedimento cirúrgico. Desfechos: 1. Manutenção de incontinência fecal retentiva em uso de enemas; 2. Controle da incontinência fecal retentiva em uso de enemas; e 3. Controle da incontinência fecal retentiva, evacuações espontâneas, sem necessidade de enemas. Resultados: Seis e 12 meses após opção terapêutica, controle da incontinência fecal retentiva foi observado apenas nos pacientes operados, 11/17 e 14/17, p = 0,001 e p = 0,001. Aos 24 meses, controle da incontinência fecal retentiva também mais frequente nos operados 13/17 versus 3/11 tratamento clínico, p = 0,005. Na avaliação final, medianas de tempo de seguimento: 2,6 e 3 anos (operados versus tratamento clínico, p = 0,40), um paciente em cada grupo abandonou o seguimento e 9/16 operados apresentavam evacuações espontâneas versus 3/10 no tratamento clínico, p = 0,043. Complicações cirúrgicas, 42 episódios, acometeram 14/17 pacientes. Conclusão: A apendicostomia, embora associada a elevada frequência de complicações, controlou a incontinência fecal retentiva de maneira mais precoce e frequente do que o tratamento clínico. A escolha de um dos métodos deverá caber à família, após adequada informação sobre riscos e benefícios de cada alternativa. Keywords: Functional constipation, Enema, Child, Adolescent, Fecal incontinence, Palavras‐chave: Constipação intestinal, Enema, Criança, Adolescente, Incontinência fecal